The role of FIGO-PALM pathologies in heavy menstrual bleeding resistant to levonorgestrel-releasing intrauterine system (Mirena®) treatment - Özgen, Levent (The European Research Journal, 2023)
Objectives: To evaluate of the indications requiring surgical treatment after Levonorgestrel-Releasing Intrauterine System (LNG-IUS) (Mirena®) treatment due to heavy menstrual bleeding. Methods: This retrospectively designed study was created with 72 patients who applied to the university hospital gynecology outpatient clinics between January 2018 and April 2019 and were diagnosed with heavy menstrual bleeding and received LNG IUS (Mirena®) for treatment. Results: Surgery was not performed in 60 (83.33%) patients who had heavy menstrual bleeding and underlying organic pathology (FIGO-PALM group) These patients were treated with LNG-IUS. However, in 12 (16.67%) patients, LNG-IUS was removed and surgery was performed due to resistance to treatment within an average of 10.2 ± 8.0 months. There was no difference between the groups in terms of age, gravida, parity, body mass index and endometrial thickness p > 0.05 for all parameters), but the mean hemoglobin value in the surgical group was found to be significantly lower than the group without it (8.9 ± 1.2 g/dL vs 11 ± 1.6 g/dL, p = 0.03) In the surgical group, the median diameters of leiomyoma and myoma compressing the endometrium were found to be significantly higher (44 mm vs 34 mm, p = 0.03 and 42 mm vs 33 mm, p = 0.04; respectively). Conclusions: LNG-IUS (Mirena®) is a popular and effective treatment option for heavy menstrual bleeding. The necessity of surgical treatment due to resistance to LNG-IUS revealed that the underlying organic pathologies in these patients should be determined precisely and effective treatment options should be carefully selected before LNG-IUS is inserted.